A74 INCREASING RATES OF CT IMAGING IN THE EMERGENCY DEPARTMENT AMONG PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (4th March 2021) - Kandel, R; Merlano, M; Tan, P; Brar, G; McCurdy, J D
Abstract: Background: Computed tomography (CT) imaging of the abdomen is often performed in the emergency department (ED) to exclude urgent pathology in patients with Inflammatory Bowel Disease (IBD). However, concerns over excessive radiation exposure from repeated use have led to expert consensus guidelines advising against CT imaging unless there is suspicion of complications (obstruction, perforation, abscess) or a non-IBD cause for symptoms. Aims: Our study aimed to determine trends in abdominal CT utilization and findings among patients with IBD in the ED. Methods: We performed a retrospective cohort study between 01/01/2009 and 31/12/2018 at a single academic center. We identified ED encounters for adults (age ≥17 years) with a pre-existing diagnosis of IBD from our institutional database and determined the proportion resulting in an abdominal CT scan within 72 hours of presentation. IBD subtypes were classified based on ICD-10 claims: K50.90* for Crohn's disease (CD), K51.90* for Ulcerative colitis (UC) and IBD undifferentiated (IBDU) for patients with both claims. A time trend analysis was performed using a generalized linear model that assumed a Poisson distribution. CT scans were classified according to the dominant imaging finding. For this part we excluded studies performed within 1-month of surgery or those re-assessing a known abscess or malignancy. Results: A total of 14783 encounters were identified. Among these encounters 3000 CT scans were performed: 2000 for patients with CD (21.9%), 652 for UC (16.5%) and 348 for IBDU (20.4%). The rates of CT utilization significantly increased by 2.7% (95% CI, 1.2–4.3; p=0.0004) in patients with CD, by 4.2% (95% CI, 1.7–6.7; p=0.0009) in patients with UC and by 6.3% in patients with IBDU (95% CI, 2.5–10.0; p=0.0011). Among the eligible CT scans performed for CD, the following dominant findings were reported: normal (25%), inflammation (23%), obstruction (23%), penetrating (18%) and unrelated to IBD (8.6%). In contrast, the following findings for patients with UC were reported: normal (20%), inflammation (39%), obstructive (19%), penetrating (8%) and unrelated to IBD (15%). Conclusions: In this single center study, a steady increase in CT utilization in the ED was observed in patients with IBD. Interestingly, only a small proportion of the CT scans demonstrated urgent findings. Future studies are required to determine the factors that contribute to the ongoing increase in CT utilization in this patient population. Funding Agencies: None